Morphological integration of the hominoid postcranium. Issue 171 (October 2022) - Conaway, Mark A.; von Cramon-Taubadel, Noreen
Abstract: Previous research has suggested that magnitudes of integration may be distinct in the postcranium of hominoids when compared to other primate species. To test this hypothesis, we estimated and compared magnitudes of integration of eight postcranial bones from three-dimensional surface scans for 57 Hylobates lar, 58 Gorilla gorilla, 60 Pan troglodytes, 60 Homo sapiens, 60 Chlorocebus pygerythrus, and 60 Macaca fascicularis . We tested the hypotheses that 1) magnitudes of integration would be distinct in the postcranium of hominoids compared to cercopithecoids, with the explicit prediction that magnitudes of integration would be lower in hominoids than in cercopithecoids, and 2) girdle elements (scapula, os coxa) would have lower magnitudes of integration across all taxa. Integration was quantified using the integration coefficient of variation from interlandmark distances reflecting anatomical and developmental modules defined according to a priori criteria. A resampling protocol was employed to generate distributions of integration values that were then compared statistically using Mann–Whitney U tests with Bonferroni adjustment. Support for hypothesis 1 was mixed: with the exception of Gorilla, hominoid taxa were less integrated than the cercopithecoids for all anatomical modules. However, Homo, Gorilla, and, to a lesser extent, Pan showed higher integration than Hylobates and the cercopithecoids for homologous limb elements, with magnitudes of integration for both modules being lowest for Hylobates . These results generally support the hypothesis of distinct patterns of magnitudes of integration in the hominoid postcranium. The high integration of Gorilla may be explained by the effects of overall body size. The results supported the predictions of the second hypothesis. Regardless of taxon, the os coxa and scapula were generally the least integrated skeletal elements, while the femur and radius were the most integrated. The lower integration of the girdle elements suggests that the geometric complexities of particular elements may significantly influence study outcomes.